Landscape Heritage in Vitória: Conservation of the Maruípe Garden - Nemer, Luciana (Revista Nacional de Gerenciamento de Cidades, 2020)
The work reveals the history of the Horto de Maruípe Municipal Park in the city of Vitória - ES. The text refers to the old Fazenda Maruípe that became Horto de Maruípe, later Parque Municipal Maruípe; highlights the main actors involved in the process and aspects related to the conservation of the landscape heritage. The research reaches the present day checking the uses of the area practiced in normal times and in the "new normal". The methodology includes consultations with secondary sources (books, articles and newspapers), iconographic and cartographic research carried out in the archives of the municipality and the state, as well as field trips. The conclusions highlight how much the park, as a morphological element of the urban space, constitutes the meeting place and leisure for residents of the neighborhood and surroundings, and also of the city, its transformations over 100 years and how much, in endemic times, the valorization of open, ventilated areas, illuminated by sunlight and quite spacious becomes even more important for society.